Assessment of vulnerability perceptions of hero health worker mothers in the COVID-19 pandemic process - Yavaş Celik, Melike; Cigdem, Zerrin (Routledge, 2023)
This study aimed to evaluate the vulnerability perceptions of healthcare mothers with children aged between 4–8 years. The population (n = 589) of the study was all healthcare workers in a hospital, while the sample (n = 342) included the healthcare worker mothers who volunteered to participate in the study, have child are 4–8 age, who could be reached through social media. According to the participants, they needed psychological support and the measures taken for COVID-19 were inadequate. The study found that the participants’ perception of vulnerability was high and that the participants who were in the 21–35 age group and who needed psychological support had high vulnerability perception. In conclusion, this study underlined some of the difficulties experienced by healthcare workers and revealed that their perception of vulnerability was high. Healthcare mothers are faced with the perception of vulnerability due to both the intense working conditions they experience and the threat of a deadly epidemic. © 2023 Taylor & Francis Group, LLC.
Keywords: COVID-19; healthcare worker mothers; perception of vulnerability